Air particulate matter exacerbates lung response on Sjögren's Syndrome animals - Ferraro, Sebastián Ariel (2014)
Epidemiological studies have associated air particulate matter (PM) inhalation with a decline in lung function and increased morbo-mortality due to cardiorespiratory diseases, particularly in susceptible populations. Sjögren´s Syndrome (SS) is a chronic autoimmune disease characterized by cellular infiltration in exocrine glands and extraglandular tissue, being the respiratory tract an important target. We evaluated the effect of PM on the airways of NOD mice, which develop SS and BALB/c mice. BALB/c or NOD mice (2-3 months) were randomized in two groups and exposed to intranasal instillation either with saline (control) or ROFA solution (1mg/kg body weight). After 24h, mice were euthanized in order to perform lung histology, or measure total cell number (TCN), differential cell count (DCC) and superoxide anion generation in the bronchoalveolar lavage (BAL) fluid. BALB/c mice showed normal histoarchitecture, while NOD mice showed lymphocytic peribronchial infiltrates. ROFA exposure affected the respiratory tract from both BALB/c and NOD mice, with a significant increase in the TCN (p<0.05) and generation of O2- (p<0.05), as well as an imbalance in the DCC (p<0.05). All histological observations correlated with the cellular parameters evaluated. Lesions in NOD mice were more severe than those of BALB/c, showing cellular infiltration in the alveoli and leading to a greater decrease in the alveolar space. We have proved that in this experimental Sjögren´s Syndrome animal model (NOD mice); airborne pollution exacerbates pre-existing pulmonary lesions. These findings show experimental evidence on the harmful effects of airborne pollution on the airways of patients with Sjögren´s Syndrome.